Aerodynamics principles for air transport pilots - Davies, Rose G. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
Equipping readers with the ability to analyze the aerodynamic forces on an aircraft, the book provides comprehensive knowledge of the characteristics of subsonic and supersonic airflow. This book begins with the fundamental physics principles of aerodynamics, then introduces the Continuity Equation, Energy Equations, and Bernoulli's Equation, which form the basic aerodynamic principles for subsonic airflow. It provides a thorough understanding of the forces acting on an aircraft across a range of speeds and their effects on the aircraft's performance, including a discussion on the difference in aerofoil and aircraft shapes. Aircraft stability issues are analyzed, along with the development of a boundary layer over an aerofoil, the changes of air speed and air pressure, and boundary layer separation. Readers will gain a clear understanding of the nature of airflow over aircraft during subsonic, transonic, and supersonic flight. The book emphasizes the connection between operating actions in flight and aerodynamic requirements. The content will be of interest to senior undergraduates studying to obtain their Airline Transport Pilot License (ATPL)/Airline Transport Pilot (ATP) certificate, general aviation and air transport pilots, and aircraft maintenance engineers.
OCLC-licensed vendor bibliographic record.
Keywords: Aerodynamics; Airplanes -- Piloting; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Health & Safety